Online Patient Education Materials for Common Sports Injuries Are Written at Too-High of a Reading Level: A Systematic Review - Youssef Abdullah, B.S; Aaron Alokozai, B.S; Samantha O'Connell, M.S; Mary K. Mulcahey, M.D., F.A.A.O.S., F.A.O.A (Elsevier, 2022)
Purpose: To determine the readability of online patient information for common sports injuries. Methods: A systematic search of the literature using PubMed/MEDLINE, Embase, and the CINAHL databases was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Studies were included if they (1) were published between 2000 and September 2020, (2) were English-language publications and complete studies from peer-reviewed journals, (3) evaluated online information directed toward patients with common sports injuries. Results: Eleven studies met inclusion criteria and were included. The mean Flesch-Kincaid Grade Level for online education information was 10.5, whereas the mean Flesch Reading Ease was 51.2, indicating existing health resources are written above the recommended readability grade level (no greater than a sixth-grade reading level). The mean DISCERN score was 41.5, indicating that the quality of information accessible to patients was fair. The accuracy of health content determined by the ACL-Specific Score was reported as moderate level (mean 8.85). Conclusions: This study demonstrates that online patient information regarding common sports injuries the does not match the readability recommendations of the American Medical Association and National Institutes of health. Clinical Relevance: Future health-related information should be written by qualified experts at a level that can be easily understood by patients of all health literacy levels. Surgeons should be more attentive to where patients get their information from and how they interpret it. Accurate, easy to understand educational tools can improve efforts to help patients identify misconceptions about treatment options, and to guide patients to choices that are consistent with their values.